2001
DOI: 10.1016/s0014-5793(01)02390-0
|View full text |Cite
|
Sign up to set email alerts
|

A thermostable K+‐stimulated vacuolar‐type pyrophosphatase from the hyperthermophilic bacterium Thermotoga maritima

Abstract: Current evidence suggests the occurrence of two classes of vacuolar-type H + -translocating inorganic pyrophosphatases (V-PPases) : K + -insensitive proteins, identified in eukaryotes, bacteria and archaea, and K + -stimulated V-PPases, identified to date only in eukaryotes. Here, we describe the functional characterization of a thermostable V-PPase from the anaerobic hyperthermophilic bacterium Thermotoga maritima by heterologous expression in Saccharomyces cerevisiae. The activity of this 71-kDa membrane-emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 28 publications
1
37
0
1
Order By: Relevance
“…sPPases have been identified in prokaryotes, plastids, and mitochondria of diverse eukaryotes and the cytosol of animal and fungal cells (4). H ϩ -PPases have been reported to occur in different groups of eubacteria and archaea (5)(6)(7)(8) and in internal (vacuo-lysosomal) membranes of higher plants (5,9,10) and diverse photosynthetic and nonphotosynthetic protists (11,12). Two distinct biochemical subclasses of H ϩ -PPases have been characterized to date: K ϩ -stimulated (3,7,11,12) and K ϩ -insensitive (6,9,14) H ϩ -PPases.…”
mentioning
confidence: 99%
“…sPPases have been identified in prokaryotes, plastids, and mitochondria of diverse eukaryotes and the cytosol of animal and fungal cells (4). H ϩ -PPases have been reported to occur in different groups of eubacteria and archaea (5)(6)(7)(8) and in internal (vacuo-lysosomal) membranes of higher plants (5,9,10) and diverse photosynthetic and nonphotosynthetic protists (11,12). Two distinct biochemical subclasses of H ϩ -PPases have been characterized to date: K ϩ -stimulated (3,7,11,12) and K ϩ -insensitive (6,9,14) H ϩ -PPases.…”
mentioning
confidence: 99%
“…Enzymes from the archeon Pyrobaculum aerophilum (36) the plant Arabidopsis thaliana (AVP2) (37) and the bacterium R. rubrum (38) are capable of PP i hydrolysis in the absence of K ϩ , whereas those from the plants A. thaliana (AVP1) (39) and Vigna radiata (40), the bacteria Thermatoga maritima (41) and Carboxydothermus hydrogenoformans (31), and the trypanosomatid T. cruzi (33) require millimolar concentrations of K ϩ for activity (31). On the basis of phylogenetic analyses of a large set of H ϩ -PPase sequences, it was suggested that K ϩ -dependent and K ϩ -independent enzymes form two independently evolving groups (35,41). A comparison of the amino acid conservation patterns in K ϩ -dependent and K ϩ -independent H ϩ -PPases revealed only two sequence positions where a residue conserved in one type is absent from the equivalent position in all the sequences from the other type (31).…”
Section: Identification Of Organelles In Bacteria 29975mentioning
confidence: 99%
“…Bacteria were post-fixed with OsO 4 for 45 min and then for 15 min with potassium ferricyanide, washed, and treated with 2% uranyl acetate for 30 min. Subsequently, the samples were dehydrated by successive incubations of 6 min with increasing concentrations of ethanol (10,25,50,75,95, and 100%) at room temperature. Epoxy embedding was carried out by resuspending the sample once in 1:1 ethanol/acetonitrile, twice in 100% acetonitrile, then 30 min in 1:1 Epoxy/acetonitrile, 1.5 h in 3:1 Epoxy/acetonitrile, and 4 h in 100% Epoxy.…”
Section: Three-dimensional Confocal Immunofluorescence Microscopy Recmentioning
confidence: 99%
“…Fixed bacteria were washed with Dulbecco's PBS and dehydrated by successive incubations of 6 min each with increasing concentrations of ethanol (10,25,50,75,95, 100, and 100%) at Ϫ20°C. The samples were embedded in Unicryl at 4°C by incubation with 1:1 ethanol/Unicryl for 1 h and 100% Unicryl for 1, 16, and 8 h. The embedded samples were polymerized under UV irradiation at Ϫ20°C for 48 h. Thin sections were collected on 300-mesh nickel grids and blocked for 30 min with PBS containing 0.1% Tween 20 and 0.5% cold fish gelatin (PBS-TW-FG).…”
Section: Three-dimensional Confocal Immunofluorescence Microscopy Recmentioning
confidence: 99%